Colloidal Hydroxyapatite/Poly(Acrylic Acid) Hybrids Using Calcium Sucrate and Ammoniumdihydrogen Orthophosphate - Wijesinghe, W.P.S.L.; Mantilaka, M.M.M.G.P.G.; Weerasinghe, A.M.C.P.; Silva, K.M. Nalin de; Gamagedara, T.P.; Rajapakse, R.M.G. (Journal of Applied Solution Chemistry and Modeling, 2016)
This manuscript is concerned with a simple and novel method to synthesize hydroxyapatite-poly(acylic acid) hybrid materials for broad range of applications. In this method, hydroxyapatite nanoparticles are synthesized using calcium sucrate and ammoniumdihydrogen orthophosphate in the presence of poly(acrylic acid). Increase in poly(acrylic acid) concentration in the synthesis medium results in the increase in the hydrodynamic radius of particle size allowing increased hydration. Poly(acylic acid) tends to control both crystallite size and colloidal stability. Increase in poly(acrylic acid) concentration decreases the crystallite size of the products but considerably increases their shelf life as stable colloidal solutions. Thermo gravimetric analysis shows that there are no combustible or volatile impurities present in these samples. This is further supported by FT-IR studies, which show three types of interactions between hydroxyapatite nanoparticles and poly(acrylic acid).